Pengaruh Latihan Kekuatan Otot Lengan Terhadap Kemampuan Servis Bawah Pada Siswa Ekstrakurikuler Bola Voli Smp Negeri 4 Muara Enim - Attiyya Ghina Widia; Bambang Hermansah; Puput Sekar Sari (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The problem in this research is whether there is an effect of arm muscle strength training on the lower serve ability of volleyball extracurricular students at SMP Negeri 4 Muara Enim. This study aims to determine the effect of arm muscle strength training on lower serve ability in volleyball extracurricular students at SMP Negeri 4 Muara Enim. This type of research is experimental research, using a one group pretest-posttest design method. The population in this study were extracurricular volleyball students at SMP Negeri 4 Muara Enim, totaling 45 people with 25 boys and 20 girls. Meanwhile, the sample in this study were all male students who took part in extracurricular activities in class VII, class VIII and class IX with a total of 25 students. The sampling technique in this research uses a purposive sample technique. The data collection technique uses the lower serve test method in volleyball. The data analysis technique uses the t test formula. Based on the results of research conducted on volleyball extracurricular students at SMP Negeri 4 Muara Enim, the average pretest result was 12.46 and the average posttest was 19.9. This shows that bicep curl training can improve the ability to serve under the ball game. volleyball among volleyball extracurricular students at SMP Negeri 4 Muara Enim. Because there was an increase after being given treatment compared to before being given treatment. In hypothesis testing, the value obtained was tcount > ttable or 31.93 > 1.71 so that it could be concluded that there was an influence of arm muscle strength training on the lower serve ability of volleyball extracurricular students at SMP Negeri 4 Muara Enim.